2013
DOI: 10.1371/journal.pone.0083907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Training on Heart Rate Recovery in Patients with Established Heart Disease; a Systematic Review

Abstract: BackgroundAlthough a delayed decrease in heart rate during the first minute after graded exercise has been identified as a powerful predictor of overall mortality in cardiac patients, the potential to influence this risk factor by aerobic training remains to be proven.ObjectiveThe aim was to study the relationship between aerobic training and Heart Rate Recovery (HRR) in patients with established heart disease.Methods(Quasi) randomized clinical trials on aerobic exercise training in adults with established hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(36 reference statements)
1
21
0
1
Order By: Relevance
“…A comprehensive literature search of PubMed, Cochrane Library, and Web of Science for English‐language studies was performed through its inception to August 2016 with the use of search terms modified from published systematic review or meta‐analysis as follows: (“heart rate recovery”) and (risk or cox or hazard or “survival analysis” or odds) (Table ). Bibliographies of selected articles and related reviews were manually checked to identify additional studies.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive literature search of PubMed, Cochrane Library, and Web of Science for English‐language studies was performed through its inception to August 2016 with the use of search terms modified from published systematic review or meta‐analysis as follows: (“heart rate recovery”) and (risk or cox or hazard or “survival analysis” or odds) (Table ). Bibliographies of selected articles and related reviews were manually checked to identify additional studies.…”
Section: Methodsmentioning
confidence: 99%
“…Increased vagal activity associated with a faster HRR has been shown to be associated with a decrease in risk of death (34). In a systemic view it was found that HRR is considerably reduced after an aerobic exercise programme in patients with established heart disease (35). It was also demonstrated that HRR at 1-2 min recovery is a prognostic measurement (36).…”
Section: Fitness and Exercise Capacitymentioning
confidence: 99%
“…Physiological measures that are readily available may help identify at-risk individuals, monitor their health changes, and evaluate the effectiveness of health interventions. HRR and HRV from 10-s ECGs are relatively easy to obtain, have been demonstrated to be responsive to exercise training (Bellenger et al, 2016;Snoek et al, 2013), and therefore may have such utility in lung cancer patients. Unlike HRR, HRV can be obtained at rest and therefore is not subjected to variations in patient effort associated with exercise testing.…”
Section: Discussionmentioning
confidence: 99%